Inception meeting for the development of the state of Odisha, India, Livestock Master Plan - CGIAR Research Program on Livestock (2020)
The livestock master plan development process for the state of Odisha, India, was launched in October 2020. ILRI leads the modelling component and sits on the technical committee (see https://www.ilri.org/livestock-master-plans).